Fundamentals of engineering thermodynamics - Moran, Michael J. (John Wiley & Sons, 1993)
Using a classical viewpoint, this Second Edition offers a comprehensive treatment of engineering thermodynamics in order to provide a sound basis for subsequent courses in heat transfer and fluid mechanics and to prepare students to use thermodynamics in professional practice. New features include more than 1300 end-of-chapter problems ranging from confidence-building exercises to more challenging issues that may involve systems with several components, including numerous problems requiring the use of a computer; over 100 design and open-ended problems which are intended as brief design experiences affording students opportunities to develop their engineering judgment and creativity; the International Temperature Scale and refrigerant material; plus interactive software designed to reinforce important ideas and hone students' problem-solving skills.